Efficacy and Safety of Peroral Pancreatoscopy Through the Fistula Created by Endoscopic Ultrasound–Guided Pancreaticogastrostomy. Issue 3 (March 2022) - Suzuki, Akinori; Ishii, Shigeto; Fujisawa, Toshio; Saito, Hiroaki; Takasaki, Yusuke; Takahashi, Sho; Yamagata, Wataru; Ochiai, Kazushige; Tomishima, Ko; Isayama, Hiroyuki
Abstract : Objectives: Endoscopic ultrasound/endosonography-guided pancreaticogastrostomy (EUS-PGS) is a useful alternative when endoscopic retrograde pancreatography is difficult. Recently, many procedures, including peroral pancreatoscopy (POPS), have been performed through the mature fistula (MF) created by EUS-PGS. We evaluate the efficacy and safety of POPS to diagnose and treat pancreatic ductal stricture/pancreato-jejunal anastomotic stricture (PDS/PJAS) through the MF. Methods: Twenty patients underwent EUS-PGS; 13 of these underwent POPS through the MF at Juntendo University Hospital. All patients were studied retrospectively in terms of technical and clinical success rates and adverse events (AEs). Results: The technical and clinical success rates of EUS-PGS were 95% and 100%. The early and late AEs rates were 20% and 15%. The technical success rate of POPS was 100%, with one AE. Biopsy of PDS/PJAS under POPS guidance revealed recurrent/residual intrapapillary mucinous adenoma (3 patients) and benign fibrotic stricture (10 patients). In the latter patients, multiple plastic stents were placed to dilate PDS/PJAS. Four patients with improvement of PDS/PJAS were stent free, but the remaining patients were not yet. Conclusions: Endoscopic ultrasound/endosonography-guided pancreaticogastrostomy and various procedures (including POPS) performed through the MF are feasible and effective and can diagnose and treat PDS/PJAS with acceptable AEs rates.